Compliance with The Implementation of Covid-19 Health Protocol Infection Prevention and Control (IPC) Training and Occupational Safety and Health (OSH) as Mediation on Occupational Risks of Health Workers at Tengku Rafi'an Hospital - Benny Chairuddin; Kemala Rita Wahidi; Natsir Nugroho (Syntax Corporation Indonesia, 2022)
There are still employees who do not understand Covid-19 prevention and control protocol in hospitals and are not disciplined in carrying out Covid-19 health protocol. IPC training implementation that has not been appropriately structured is considered the cause of some employees being exposed to Covid-19. This study aims to analyze the effect of compliance Covid-19 health protocol implementation and the implementation of Infection Prevention and Control training on the occupational risks of health workers and Occupational Health and Safety standards implementation as intervening variables in the Covid-19 pandemic era at Tengku Rafi'an Regional Public Hospital simultaneously and partially. This research method is causative descriptive research with a quantitative study approach. The sample of this study was 200 health workers who work in hospitals. The data analysis technique used is index analysis using the three-box method and Structural Equation Modeling (SEM) for path analysis. Conclusion of this study showed the implementation of the Covid-19 Health Protocol, IPC Training, and Occupational Safety and Health Standards implementation together significantly affected the Occupational Risks of Health Workers simultaneously and partially at Tengku Rafi'an Regional Public.